Social Classes Inequality In The English-Translated Version By Bett And Boyd Of Kawakami’s Japanese Novel Entitled “Heaven” - Putri, Hurul Aini; Sugaryamah, Deuis; Pramita, Agry (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
Heaven is a Japanese novel authored by Mieko Kawakami in 2009, translated by Bett and Boyd in 2020. Kawakami identifies bullying in schools, particularly through the character Iijima, as the central theme of this story. Moreover, the phenomenon of bullying stems from the fundamental issue of social class inequality. This research aims to: 1) identify social class through the frameworks of Marx and Levy, Jr.; 2) elucidate Kawakami's perspective and the concept of transindividuality; and 3) assess the significance of social class inequality in translation practices. This research method employs a descriptive qualitative approach, which focuses on social analysis. However, it persuades social classes to comprehend analysis and utilize sociology literature and literary translation from the perspective of an English learner. This research identifies the highest class as Ninomiya, who is a facilitator of bullying, while the lowest class is represented by Eyes and Kojima, who suffer from bullying. Kawakami created those characters as a manifestation of her social and humanity philosophy, taking into account her own past experiences. Therefore, Bett and Boyd, as the translators of Heaven, uphold the values of social class inequality